Pelekatan Nama Uray Dalam Hukum Adat Melayu Di Kesultanan Sambas - Wibowo, Ajeng Auliya Ramadhani; Marnita; Prihatin, Angga; Lolita; Aminah, Siti (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2023)
status, and a person's contribution to society and government. In the Sambas Sultanate, derived names were automatically attached to someone who was a descendant of the Sultanate's family. One of the names known in the Sambas Sultanate and the Malay indigenous community is "Uray". However, this honorary name could later be changed to "Raden" with an appointment from the Palace. This can clearly lead to changes in the social hierarchy and a person's status in society. Through a literature study related to the attachment of honorary names known in the Malay tribal community in the Sambas Sultanate. This paper aims to (i) find out how someone gets the honorary name Uray in the Malay traditional community; (ii) the causal factors that enable a person to change his honorary name from Uray to Raden; and (iii) are there any consequences that the person will receive due to the change of name. The author uses an empirical legal writing method that is descriptive exploratory in nature. The results of the writing are (i) the honorary names Uray and Raden were obtained through lineage relationships; (ii) factors that cause changes in the name of honor that a person has are marital relations and direct appointment from the Palace by the Sultan; and (iii) someone who has changed his honorary name through a traditional ceremony will have new responsibilities that make him someone who plays an important role in society. One of them is being a role model in terms of cultural preservation.